Finding voice, vocabulary and community. The UWC Student Movement 1972-1976 - Thomas, Cornelius (Faculty of the Humanities, University of the Free State, 2014)
This article delves into an activist vocabulary adopted by Coloured students at the University of the Western Cape (UWC) in the early- to mid-1970s. It asks what language these students used to make meaningful in their solidaristic opposition to apartheid South Africa, and how they found their voice after the relative Coloured quiescence in the 1960s. The article specifically interrogates how, in the context of black consciousness, Coloured students acquired, appropriated and applied the concepts of “conscientization”, “black”, “liberation theology”, and “community”. Homing in on the period 1970 to 1976, it unfolds a student protest narrative, including the Demas tie affair (1970), SASO-UWC’s activism (1972-1974), the UWC students’ response to community (1975-1976), and the Soweto uprising (1976). It finds a new conversation and activism that found expression “in the community”. As an autoethnographic and qualitative narrative piece, the article scripts the unfolding of a new phenomenon in Coloured protest, one which shows a departure from an older (Non-European Unity Movement) political language and makes “audible” the student voice in community inclusive anti-apartheid activism. It shines new light on a moment in Coloured history that linked UWC students nationally and transformed the struggle in organic and instrumentalist ways.
Keywords: Concscientization; Black consciousness; Students; Activism; Protest(-s); Liberation theology; Community; Apartheid